THE IMPACT OF TARGET MARKETS, UNIQUE RESOURCES & MARKET ATTRACTION ON DIGITAL MARKETING: THEIR SIGNIFICANCE FOR SELECTING POSTSECONDARY EDUCATION - Erpurini, Wala; Juju, Undang (Jurnal Riset Bisnis dan Manajemen, 2024)
Due to competition, universities in the Bandung Raya metropolitan area have integrated digital marketing into their curricula. This unique study investigates variables not previously explored in private universities. It aims to guide educational institutions in enhancing digital marketing strategies to attract prospective students. Digital marketing effectiveness is evaluated based on market attractiveness, target market, and resource uniqueness. SEM analysis reveals that Market Attractiveness directly influences by 11.88% and indirectly by 6.54% through Target Market and 6.67% through Resource Uniqueness. Resource Uniqueness also impacts indirectly by 6.67% via Market Attractiveness and 5.85% via Target Market, and directly by 12.95%. The Target Market shows a direct effect of 11.36%, with indirect effects of 5.85% through market attractiveness and 6.54% through resource uniqueness. This study innovatively links and refines these five concepts.